The Development And Effect Of Simulation-Based E-Learning Interactive Training On Students’ Perception And Technological Skills - Emara, Noran Adel Abd Elrahman (2018)
The main objective of the research is to examine the effect of Simulation-based E-learning Interactive Training (SBEIT) on undergraduate students’ perception and technology skills in Technology course. The researcher developed two e-learning modes: E-learning Traditional Training (ETT) and Simulation-based E-learning Interactive Training (SBEIT). The researcher used number of Adobe programs to design and develop both ETT and SBEIT modes which latter on delivered through the Blackboard (BB) Learning Management System (LMS). The researcher, with the help of panel of experts developed technology skills questionnaire and technology skills test which were used to test four classes of Technology course before and after the treatment.